2011
DOI: 10.1242/jcs.041244
|View full text |Cite
|
Sign up to set email alerts
|

Insights into intermediate filament regulation from development to ageing

Abstract: SummaryIntermediate filament (IF) proteins comprise a large family with more than 70 members. Initially, IFs were assumed to provide only structural reinforcement for the cell. However, IFs are now known to be dynamic structures that are involved in a wide range of cellular processes during all stages of life, from development to ageing, and during homeostasis and stress. This Commentary discusses some lesser-known functional and regulatory aspects of IFs. We specifically address the emerging roles of nestin i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 163 publications
5
30
0
Order By: Relevance
“…The view that vimentin potentiates Jagged function is corroborated by the data showing that Jagged expression correlates with vimentin expression in several tissues and in cancer, in particular. Elevated expression of both vimentin and Jagged has been implicated in tumor progression (6,8,10,16,(73)(74)(75)(76). Furthermore, observations in vimentin knockout mice links vimentin to defects in wound healing, fibrosis, inflammation, epidermal aging, and epithelial mesenchymal transition in cancer (4,7,8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The view that vimentin potentiates Jagged function is corroborated by the data showing that Jagged expression correlates with vimentin expression in several tissues and in cancer, in particular. Elevated expression of both vimentin and Jagged has been implicated in tumor progression (6,8,10,16,(73)(74)(75)(76). Furthermore, observations in vimentin knockout mice links vimentin to defects in wound healing, fibrosis, inflammation, epidermal aging, and epithelial mesenchymal transition in cancer (4,7,8).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas IFs provide cells with mechanical stability, there is mounting evidence indicating that IFs are involved in a range of metabolic, signaling, and regulatory processes that are unrelated to mechanical functions (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). The vimentin IF has been shown to act as a scaffold for signaling proteins that regulate epithelial mesenchymal transition (EMT), cancer cell invasion, wound healing and tissue repair, tissue aging, as well as inflammatory signaling (3,4,(6)(7)(8)10).…”
mentioning
confidence: 99%
“…In light of our results, we suggest that pS71-vimentin is important for chemotaxis. This might be because vimentin is important for cell motility, with a role in organising receptor molecules on the cell membrane and in the cellular localisation of adhesion-associated molecules and migration-regulating kinases (Hyder et al, 2011;Nieminen et al, 2006;Pallari and Eriksson, 2006;Sin et al, 1998). The exact role of vimentin phosphorylation in these processes remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Another member of the intermediate filament family, vimentin, has well established roles in migratory signalling and processes, often acting in concert with K8/K18 (Hyder et al, 2011;Ivaska et al, 2007;Pallari and Eriksson, 2006). Interestingly, an early study indicated that S1P caused vimentin filament reorganisation (Sin et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…1 The IFs share a common structure consisting of a structurally conserved rod domain flanked by variable head and tail regions. 2 Except for the lamins all IFs are cytoplasmic proteins that are part of the cytoskeleton.…”
Section: Lamins Are Intermediate Filament Proteinsmentioning
confidence: 99%